Rule of Law and Criteria for Definition of Law In the views of Friedrich Karl von Savin (Historical School of Law) - Gabisonia, Lali (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
The present paper is devoted to the views of a prominent representative of the Historical School of Law on such important issues as the theory of law and the philosophy of law, such as the origin of law, its existence, and the criteria for defining the rule of law. Friedrich Carl von Savin has left an indelible mark on the creation of the historical school of law, as well as his great contribution to the understanding of the historical or theoretical aspects of the origin of law. The Historical School of Law was founded in the late 18th and early 19th centuries and was founded by German lawyers Gustav Hugo, Friedrich Carl von Savin and Georg Friedrich Puchta. The strength of the historical school of law is the fact that they paid great attention to law as an event, scientifically investigated the origin of law, became the object of their interest in the so-called Positive law and the real reasons for its origin. Today it is inconceivable for the world to exist without the existence of law, without its practical application. The practical application of law begins with its correct reading and correct interpretation. The practical application of law is the main result of the pursuit of jurisprudence as a science and law as a set of mandatory rules of conduct governing public relations. Interesting and noteworthy are the Friedrich Karl von Savinian criteria for the definition of law. Methodologically, the definition of law is one of the most important and complex processes, which requires a correct, consistent, hierarchy of existing methods and methods of definitions in a certain sequence, and an appropriate interpretation of each case to be regulated. In this sense, finding the relevant norm of the law governing a particular relationship and just reading it is not enough, establishing the fact and selecting the norm is simply written on paper, in real life, in legal work, I think, the most difficult, responsible, Variable process.